PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DIMASA PANDEMI COVID 19 PADA STEFANI CITY HOTEL PEKANBARU - Sri Suryani; Lie Othman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at Stefani City Hotel Pekanbaru located at Jalan Taskurun No. 100, Wonorejo, Kec. Marpoyan Damai, Pekanbaru City, Riau. The purpose of this study was to determine the effect of service quality on consumer satisfaction at Stefni City Hotel Pekanbaru. In this research, the method used is descriptive quantitative analysis with SPSS program. The population in this study were all visitors who were visiting at Stefani City Hotel Pekanbaru in 2021 as many as 7,542 people. Where the sample in this study were all visitors to Stefni City Hotel Pekanbaru as many as 99 respondents. Data collection techniques through questionnaires, types and sources of data using primary data and secondary data, measurement data collection techniques using a Likert scale.The problem in this study is the decline in visitors to Stefani City Hotel Pekanbaru in the last year. It can be seen from the visitor and sales data and the score table given by the consumers. From the results of the tests conducted, it shows that the effect of service quality has a positive and significant effect on customer satisfaction at Stefani City Hotel Pekanbaru.Keywords: Service Quality, Consumer Satisfaction